2020
DOI: 10.3390/jcm9072040
|View full text |Cite
|
Sign up to set email alerts
|

Association of Systemic Comorbidities with Dry Eye Disease

Abstract: We investigated the association between dry eye disease and systemic comorbidities, including dry eye subtype, quality of life (QOL) and health utility among patients with dry eye disease. This cross-sectional, observational study enrolled 449 patients with dry eye disease (386 females; mean age, 62.6 ± 15.7 [range, 21–90] years). Ophthalmic examination findings included tear film break-up time (TBUT), Schirmer I value and keratoconjunctival staining score. QOL and health utility were evaluated using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The observed high prevalence of DED with VDT use could, however, also be due to confounding factors such as CL wear, use of air conditioning and poor indoor climate including pollutants, allergens and low humidity (Bron et al 2017;Idarraga et al 2020;Mehra & Galor 2020). Moreover, comorbidities can be important confounders as well (Kawashima et al 2020;Mehra & Galor 2020). A recent large population-based study by Bazeer et al, that investigated the association between type of occupation and symptomatic DED, found a highly significant positive association between occupations relying on VDT use (such as customer service clerks and other administrative occupations) and symptomatic DED.…”
Section: Discussionmentioning
confidence: 99%
“…The observed high prevalence of DED with VDT use could, however, also be due to confounding factors such as CL wear, use of air conditioning and poor indoor climate including pollutants, allergens and low humidity (Bron et al 2017;Idarraga et al 2020;Mehra & Galor 2020). Moreover, comorbidities can be important confounders as well (Kawashima et al 2020;Mehra & Galor 2020). A recent large population-based study by Bazeer et al, that investigated the association between type of occupation and symptomatic DED, found a highly significant positive association between occupations relying on VDT use (such as customer service clerks and other administrative occupations) and symptomatic DED.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also found that use of sleep medications in the sleep disorders was significantly associated with DED. Kawashima et al have demonstrated that sedative antidepressants could significantly decreased tear break-up time of DED patients (29). Antidepressants could promote dry eye symptoms through anticholinergic side effects (inhibition of cholinergic nerve fibers in meibomian and lacrimal glands) or other potential pharmacological mechanisms to reduce tear secretion (17,30).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies were conducted in community populations or cohort populations by collecting questionnaires on sleep and dry eye symptoms (19,20,26,27), however these studies may have drawbacks of selection bias and recall bias. There are also studies suggesting that sedative antidepressants would promote dry eye symptoms and signs (17,(29)(30)(31). In the current study, we would like to compare the incidence of DED that developed in participants with or without sleep disorders, using the integrated health care network system data, and evaluate whether sleep disorders was a risk factor for DED.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological reports suggest that the prevalence of DED ranges from 5% to 50% in general population across the world [1,[3][4][5][6][7][8][9]. The large variation in prevalence is due to the differences of diagnostic criteria, characteristics of investigated participants and etiological factors [10][11][12]. The most prevalent form of dry eye (DE) is evaporative dry eye (EDE), accounting up to two-thirds of all DE cases, mostly due to meibomian gland dysfunction (MGD) [13][14][15].…”
Section: Introductionmentioning
confidence: 99%